Reducing oxidative stress and hepatoprotective effect of water extracts from Pu-erh tea on rats with high-fat diet - Jingjing Su; Xueqing Wang; Wenjun Song; Xiaoli Bai; Changwen Li (Food Science and Human Wellness)
Reducing oxidative stress and hepatoprotective effect of Pu-erh tea water extracts on rats fed with high-fat diet were researched for explaining health care of Pu-erh tea. Fifty SD rats were divided into five groups. The body weight was measured once a day. The malondialdehyde (MDA) and glucose (Glu) levels and the activities of alanine aminotransferase (ALT), aspartate aminotransferase (AST), nitric oxide synthase (NOS), and pyruvate kinase (PK) in serum were determined. Furthermore, the hepatic glycogen level (HGL) and the activities of hepatic total superoxide dismutase (T-SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) were also measured after continuous administration for 12 weeks. The result demonstrated that Pu-erh extract caused the decreases in body weight, fat index, MDA and NOS levels, and the increases in hepatic T-SOD, CAT and GSH-Px activities, indicating that the extract may be due to inhibiting the increases of body weight and fat index, reducing oxidant stress state and inhibiting lipid peroxidation, thus decreasing the activities of ALT and AST, and protecting the liver in rat. Meanwhile, the extracts could increase the production of hepatic glycogen and the activity of PK, and reduce glucose level, protecting the liver from the diseases associated with type II diabetes.